Categorization of compensatory motions in transradial myoelectric prosthesis users. (June 2017) - Hussaini, Ali; Zinck, Arthur; Kyberd, Peter
Background: Prosthesis users perform various compensatory motions to accommodate for the loss of the hand and wrist as well as the reduced functionality of a prosthetic hand. Objectives: Investigate different compensation strategies that are performed by prosthesis users. Study design: Comparative analysis. Methods: A total of 20 able-bodied subjects and 4 prosthesis users performed a set of bimanual activities. Movements of the trunk and head were recorded using a motion capture system and a digital video recorder. Clinical motion angles were calculated to assess the compensatory motions made by the prosthesis users. The video recording also assisted in visually identifying the compensations. Results: Compensatory motions by the prosthesis users were evident in the tasks performed (slicing and stirring activities) as compared to the benchmark of able-bodied subjects. Compensations took the form of a measured increase in range of motion, an observed adoption of a new posture during task execution, and prepositioning of items in the workspace prior to initiating a given task. Conclusion: Compensatory motions were performed by prosthesis users during the selected tasks. These can be categorized into three different types of compensations. Clinical relevance: Proper identification and classification of compensatory motions performed by prosthesis users into three distinct forms allows clinicians and researchers to accurately identify and quantify movement. It will assist in evaluating new prosthetic interventions by providing distinct terminology that is easily understood and can be shared between research institutions.